Current states and perspectives of Czech educational research - Tomáš Janík (Czech Pedagogical Society, 2010)
The aim of the review study is to evaluate the current state of Czech educationalresearch and to offer possibilities of its further development. The paper has threeparts. In the first part, the author presents the context of the topic: the current changesin the financing of research and development in the Czech Republic; the avoiding ofthe term (social) science is discussed along with the issue of institutional financing ofresearch and the various presently up-to-date methodologies of quality assessment inresearch. In the second part, the author analyses the current state of Czech educationalresearch - previous analyses of J. Pr°ucha, J. Mareš and E. Walterová and those carriedout by the Educational Research Centre are briefly summarised. In the third part, possibilitiesof further development of Czech educational research are offered. Developinga knowledge base of educational sciences is used as an example. First the nature andsubject of knowledge that is produced by research is analysed, then the difference betweenpedagogical research and research in education is discussed. Towards the end,relevant approaches are discussed along with research areas and types of knowledgeacquired by research.